Conceptual Review of Urban Molecular Organic Signatures for Environmental Forensics and Net-Zero Transition in Serpong - Rafeyfa Calla Asylacleosa Aisyhafiy; Aufa Avanina Aydani; Deni Samsudin Permana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Non-industrial satellite cities in Indonesia are commonly assessed using conventional air-quality indicators, while molecular-level evidence of diffuse urban organic pollution remains poorly synthesized. This conceptual review examines how polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), and phthalates may be interpreted as Urban Molecular Signatures (UMS) for future environmental forensic research in Serpong and comparable non-industrial urban areas. A structured narrative-integrative literature review was conducted using peer-reviewed studies on molecular fingerprinting, GC-MS-based organic pollutant analysis, PAH and VOC source attribution, phthalates as markers of domestic and synthetic materials, environmental forensics, urban metabolism, exposome-related frameworks, and Net Zero Emission (NZE) transition literature. The review shows that PAHs, VOCs, and phthalates are well-established indicators of combustion, traffic, solvent use, household activities, synthetic materials, and urban consumption patterns. However, integrated studies combining GC-MS, molecular fingerprinting, environmental forensics, and NZE-related interpretation remain very limited in Indonesia, particularly in non-industrial satellite cities such as Serpong. This paper therefore proposes UMS as a conceptual framework for interpreting mixed patterns of organic pollutants as source-pressure indicators. The framework does not claim that molecular signatures directly determine carbon neutrality or decarbonization pathways. Rather, UMS may complement future emission-inventory and mitigation studies when combined with activity data, emission factors, household behavior, mobility patterns, and policy feasibility analysis. Future research should validate this framework through systematic sampling, GC-MS analysis, diagnostic ratios, multivariate source apportionment, and local emission-activity datasets. Contribution to Sustainable Development Goals (SDGs):SDG 11: Sustainable Cities and CommunitiesSDG 15: Life on Land